(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Transcutaneous electrical nerve stimulation (TENS) is widely used as a therapeutic adjunct in the management of low back pain. It is a relatively safe, non-invasive, and easy-to-use modality, making it an attractive treatment option. For more than four decades, TENS has been applied in the treatment of acute and chronic pain syndromes. Short wave diathermy (SWD) is a modality that produces deep heating by converting electromagnetic energy to thermal energy. Short wave diathermy (SWD) is also a popular therapy for low back pain. Methods: This randomized controlled clinical trial was conducted to evaluate the comparative efficacy between TENS and SWD on chronic nonspecific low back pain patients. 120 patients with chronic low back pain were treated according to inclusion & exclusion criteria. Patients were equally distributed in three groups. Group-A patients (n=40) were treated with NSAID+ADL, Group-B patients (n=40) were treated with NSAID+ADL+TENS, and Group-C patients (n=40) were treated with NSAID+ADL+SWD. Written informed consent was obtained from all patients. Data were calculated and analyzed by computer-based software SPSS (Statistical Package for Social Science) Windows 16.0 version. Main outcome measure (s) Age, Sex, Occupational status, Socioeconomic status, Subjective pain intensity score, Visual Analogue Scale, Tenderness index, Disability due to pain, Spinal mobility index, and Oswestry disability Index. Results: The mean duration of pain was found to be 23.90±2.57 months in group A, 21.0+1.50 months in group B and 22.1±1.89 months in group C. The visual analog score was improved individually in group-A, group B and Group C after treatment, which was statistically significant (P<0.05). Oswestry disability questionnaire score was also improved individually in group-A, group B and Group C after treatment, which was statistically significant (P<0.05). In the case of comparison between group-B and Group C, this was not statistically significant (P>0.05). In this current study, it was observed that the entire variable individually improved in Group-A, Group B, and Group C. So, all three treatment groups benefited from drugs and therapy. But, these were not statistically significant (P>0.05) between Group B and Group C. Conclusion: Beneficial effects of TENS and SWD were seen in the study population, but no firm conclusion could be drawn. TAJ 2023; 36: No-2: 135-143